Biomarker-driven EGFR therapy improves outcomes in patients with metastatic colorectal cancer. Issue 9 (September 2014) - Hendifar, Andrew; Tan, Carlyn-Rose; Annamalai, Anand; Tuli, Richard
<x xml:space="preserve">Abstract</x> As new data from randomized studies comparing EGFR–targeting therapies with VEGF inhibitors emerge, the treatment landscape for metastatic colorectal cancer is expected to change. Although both the VEGF inhibitor bevacizumab and the anti-EGFR antibody cetuximab are approved in the first-line setting, they have not until recently been compared directly in randomized studies. Unlike targeted therapy in the EGFR pathway, there are no biomarkers guiding VEGF treatment. Recent data, discussed in this review, demonstrate that patients with KRAS/NRAS wild-type tumors benefit from anti-EGFR therapy in the first-line setting and that anti-EGFR therapy may be superior when compared with anti-VEGF approaches. This review focuses on the clinical utility of targeting EGFR by revisiting the biologic rationale for EGFR inhibition in metastatic colorectal cancer and providing new insight on the advancements in biomarker analyses with the potential to change practice.